ANALYZING THE CONSUMER BEHAVIOR IN TERMS OF USING CASHLESS FOR TRANSACTION AT MEGAMALL MANADO - Soputan, Miguel O. S.; Lapian, Joyce S. L. H. V.; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2021)
The worldâ€™s financial system that exists today is the result of the development and evolution a few centuries ago. Technological development has an impact on all aspects of life including changes to the existing payment system. Cash payment instrument by using money has begun to shift to non-cash payment instruments. A review of the previous literature found that most previous studies focused on investigating the respective how cash transaction replaced by cashless transaction, and few explored the influence of the interaction between these two factors concerning purchase decision making in consumer behavior. The aim of examining the interference effect of marketing stimulation on the consumer behavior affect the type of transaction by costumers in Megamall Manado. This research used quantitative and multiple regression analysis with the sample which 50 respondents that were obtained from random people who shopping at Megamall Manado. The result shows that Cashless Transaction has a significant effect on Consumer Behavior partially. Lifestyle and money attitude have a significant effect to purchase decision simultaneously. Cash Transaction has the most significant influence on the Consumer Behavior of customer at Megamall Manado. Therefore, the researcher suggestion to paying attention to this factor. People should feel satisfied and make a good choice to make a purchase payment for their safety and security. This study can be used as a reference for the development and deepening of the knowledge banking system of payment, especially to replace cash transaction with the cashless transaction or nowadays we called digital banking.Â Keywords: cashless transaction